Семь почти счастливых женщин: роман / Лидия Давыдова - Давыдова Лидия Евгеньевна (Эксмо, 2023)
Экземпляры: Ф.6\7\14\16\26 (20240808) / Инвентарный номер: 67049 / Цена: 343.00 / Сис.шифр: Р2 / Авт.знак: Д 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6